Institutional Rearing Is Associated with Lower General Life Satisfaction in Adulthood - David Richter; Sakari Lemola (Journal of Research in Personality, 2014)
We analyzed whether individuals reared in institutions differ in their general life satisfaction from people raised in their families. The data comprised of 19,210 German adults (51.5% female) aged from 17 to 101~years and were provided by the SOEP, an ongoing, nationally representative longitudinal study in Germany. Compared to people raised in families, individuals reared in institutions reported lower general life satisfaction in the manner of a dose response relationship controlling their parents' education and occupational prestige. The association was moderated by participants' age such that with increasing age the association between institutional rearing and lower general life satisfaction decreased. Further, the relationship was partly mediated by the individuals own education/socio-economic attainment in adulthood, physical health, and relationship status.
Additional information: NOTICE: This is the author's version of a work that was accepted for publication in the Journal of Research in Personality. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in the Journal of Research in Personality 48 (2014), pp. 93-97 and is online available at http://dx.doi.org/10.1016/j.jrp.2013.11.001
Keywords: 330; Life satisfaction; Set point theory; Early adversity; Institutional Rearing; Zufriedenheit; Kinder; Erwachsene